Analysis of Android-Based Science Learning Media to Improve Motivation and Learning Outcomes of Elementary School Students: A Systematic Literature Review - Miftachul Hidayah; Ana Fitrotun Nisa; Banun Havifah Cahyo Khosiyono; Akbar Al Masjid; Berliana Henu Cahyani (Jurnal Penelitian Pendidikan IPA, 2025)
According to some elementary school students, science subject matter is included in the category of difficult and less interesting material to learn. Because most of the materials in Science Lessons are abstract. This causes a lack of student motivation and suboptimal learning outcomes. Responding to these challenges, many learning media have been developed, one of which is android-based learning media which is desired to be one of the innovative solutions to overcome challenges in science learning. This study aims to analyze the validity and effectiveness of android-based learning media, especially in science learning in elementary schools in an effort to increase student motivation and learning outcomes. The methodology in this study is by means of a Systematic Literature Review (SLR) which involves 21 relevant articles that are searched using Harzing's Publish or Perish machine with scopus and crossref reference categories, then processed using the PRISMA flow. The results of this study show that all learning media written in the article show a valid and effective category for increasing student motivation and learning.